Self-medication and violent behavior - Ostrowsky, Michael K. (Criminal justice recent scholarship, 2009)
The causes and consequences of drug use -- Exploring the relationships between self-esteem, depression, alcohol use, and marijuana use -- Does alcohol use lead to violent behavior? -- Does marijuana use lead to violent behavior? -- Khantzian's self-medication hypothesis -- Overview of the study, sample, measures, and path model -- Bivariate findings regarding delf-medication and violent behavior -- Multivariate findings regarding self-medication and violent behavior -- Implications and prevention